Arterial site selection for measurement of mean arterial pressure in septic shock patients on high-dose norepinephrine - Bhaskar, Bhanuprakash; Gurjar, Mohan; Mishra, Prabhaker; Azim, Afzal; Poddar, Banani; Baronia, Arvind K. (Frontiers in Medicine, 2022)
Background The guidelines of the Surviving Sepsis Campaign suggest using invasive blood pressure (IBP) measurement in septic shock patients, without specifying for a preferred arterial site for accuracy in relation to the severity of septic shock. The objective of this study was to determine the mean arterial pressure (MAP) gradient between the femoral and radial artery sites in septic shock patients. Method This prospective study was carried out at a 20-bed ICU in a university hospital. Simultaneous MAP measurements at femoral and radial arterial sites were obtained in septic shock patients receiving norepinephrine (≥0.1 μg/kg/min), with a pre-planned subgroup analysis for those receiving a high dose of norepinephrine (≥0.3 μg/kg/min). Results The median norepinephrine dose across all 80 patients studied, including 59 patients on a high dose, was 0.4 (0.28–0.7) μg/kg/min. Overall, simultaneous measurement of MAP (mmHg) at the femoral and radial arterial sites produced mean (95% CI) MAP values of 81 (79–83) and 78 (76–80), respectively, with a mean difference of 3.3 (2.67–3.93), p < 0.001. In Bland–Altman analysis of MAP measurements, the detected effect sizes were 1.14 and 1.04 for the overall and high-dose cohorts, respectively, which indicates a significant difference between the measurements taken at each of the two arterial sites. The Pearson correlation coefficient indicated a weak but statistically significant correlation between MAP gradient and norepinephrine dose among patients receiving a high dose of norepinephrine (r = 0.289; p = 0.026; 95% CI 0.036–0.508). Conclusion In septic shock patients, MAP readings were higher at the femoral site than at the radial site, particularly in those receiving a high dose of norepinephrine. Clinical trial registration [ClinicalTrials.gov], identifier [NCT03475667].